PENYAKIT PERIODONTAL SEBAGAI PENGHAMBAT PERAWATAN ORTODONSI - Ni Made Widhiasti (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Periodontal health status is an essential factor before and during the orthodontic treatment procedure. Periodontal disease can have negative effect that is delay in any orthodontic treatment and will be unstable result. The purpose of this article is to review that the periodontal disease can be as the inhibiting of orthodontic treatment. Periodontal disease can inhibit the effectiveness of orthodontic appliances and influence to the principles of orthodontic’s biomechanics. Inflamation in the periodontal tissue cause limited tooth movement. Orthodontic treatment can not be started before inflammation in the periodontal tissue have been overcame.